Apropriação das TIC no Senegal: Sociabilidades Jovens e Valores Sociais em Crise - Falcão, Ricardo (2016)
The generalisation of Information and Communication Technologies in the world gains momentum also in Africa, in countries such as Senegal. The appropriation of ICT promotes new social dynamics, in communications, economies, circulation of ideas, and has been considered important in new forms of political participation and new models for business. But ICT, through their ability to represent the world and communication, participate also in important changes in sociabilities. In Senegal, we observe social tensions in gender and intergenerational relations, that have become apparent by a new regime of exposure of social relations and exacerbated by these technologies. A patriarchal ideology considers the openness to the world and to new cultural references problematic. The fear of cultural alienation sustains the perception of a crisis in social values. This thesis aims at questioning the dialectics between this fear and the liberating potential of ICT, by considerind the instances where social tensions are observable, namely on feminine sociabilities, linked to the body and sexuality, to public and private spaces, to generational practices and to youth, their aspirations and place in society. The crisis in social values is here thought of as an ideological construction based on a difuse and disproportionate moral panic, symptomatic of a crisis in masculinities. The analysis on the codifications of gender relations, family, conjugal, generational and neighbourly relations, configures the shift from an object centered in TIC to another one centered on the influence of TIC in social relations.